Pengaruh Arus Kas Dan Belanja Modal Terhadap Cash Holding Pada Perusahaan Manufaktur - Isabella Hadiwijaya, Estralita Trisnawati (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to examine the effect of cash flow and capital expenditure to the cash holding. The sample of this research in manufacturing companies that listed in Indonesia Stock Exchange (IDX) during the year 2012-2017. The hypothesis was examined using SPSS 23 for descriptive statistics test and SmartPLS 23 for inner and outer model test. The result of the analysis showed that cash flow and, capital expenditure have significant impact to the cash holding.